The Effectiveness of Group Counseling with the Rational Emotive Behavior Therapy (REBT) Approach to Reduce Students' Anxiety in Facing College Entrance Exams - Nilas Siti Wulandari; Dina Sukma; Zadrian Ardi; Miftahul Fikri (Postgraduate, University of Mataram, 2025)
This study aims to test the effectiveness of group counseling services using the Rational Emotive Behavior Therapy (REBT) approach in reducing students' anxiety facing college entrance exams. This study uses a quantitative approach with a quasi-experimental design with a pretest-posttest control group design. The subjects were 14 students of grade XII of SMA Pertiwi 1 Padang who had moderate to high levels of anxiety based on the initial measurement results. Data were collected using the College Entrance Exam Anxiety Scale developed to cover three main dimensions: emotional, cognitive, and physiological anxiety. This scale consists of 37 valid statements with a Cronbach's Alpha reliability value of 0.93, indicating a very high level of reliability. Data analysis was performed using the Wilcoxon Signed Rank Test and the Kolmogorov-Smirnov 2 Independent Samples Test with the help of SPSS version 26.0. The results showed a Z value = -2.36 and p = 0.01 (p < 0.05) in the experimental group, which means there was a significant difference between the anxiety levels before and after treatment. Meanwhile, there were no significant differences in the control group. These results demonstrate that group counseling services using the REBT approach are effective in reducing student anxiety, particularly in the emotional, cognitive, and physiological aspects. This approach helps students think more rationally, manage their emotions, and reduce physical symptoms of anxiety leading up to college entrance exams.